IMPLEMENTASI COMPUTER MEDIATED COMMUNICATION DALAM DIGITAL STAFFING BERBASIS MOBILE APPLICATION DAN ONLINE PLATFORM DI PERUSAHAAN STARTUP - Prabu Rabbani Kapriadi; Irwansyah Irwansyah (KAREBA : Jurnal Ilmu Komunikasi, 2020)
This journal article reviews the literature on the implementation of computer-mediated communication in electronic recruitment or digital staffing which aims to explore how the computer-mediated communication environment has been applied in optimizing its activity. In addition, there are study investigations in particular the benefits of computer-mediated communication and the factors that influence the use of computer-mediated communication in this kind of activity at  startups focused in recruitment services. This study discusses the implementation of computer-mediated communication as a forum for digital staffing. In this era of globalization, recruitment activities have shifted from traditional channels and practices to online processes. Therefore, online recruitment today has presented a series of different practices that occur on the Internet, especially in the recruitment of workers based on mobile applications and websites. This research was conducted with a qualitative method in which semi-structured interviews were conducted by interviewing three employees with various positions ranging from staff to manager level in a startup company of digital staffing. The purpose of this study is to explore the perspectives of employees regarding digital staffing based on mobile applications and communication media used in the process. This research shows that computer-mediated communication patterns cause several changes including in the conventional staffing to digital staffing through mobile applications and websites.